2020
DOI: 10.21203/rs.3.rs-35206/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Toll-Like Receptor 4 Mediated Oxidized Low-Density Lipoprotein-Induced Foam Cell Formation in Vascular Smooth Muscle Cells

Abstract: Background: Oxidized low-density lipoprotein (oxLDL) induced a foam-cell like phenotype of the vascular smooth muscle cells (VSMCs), leading to the inflammatory responses incorporating Toll-like receptors (Tlrs)-mediated cellular alterations. We previously found that Tlr4 participated in inflammation response in VSMCs under oxLDL stimulation. However, the role of Tlr4 in foam-cell formation and underlying molecular pathways has not been comprehensively elucidated. This study aimed to investigate the role of Tl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…This finding is partially supported by a report by Lee et al that genistein obviously decreased SRC phosphorylation in prostate cancer cells (38). A recent report unveiled that repressing SRC activation attenuated ox-LDL-induced lipid accumulation and foam cell formation in VSMCs (39). Concordantly, Lang et al demonstrated that the downregulation of SRC correlated to the reduced proliferation and migration of hydrogen peroxide-exposed VSMCs (40).…”
Section: Discussionsupporting
confidence: 53%
“…This finding is partially supported by a report by Lee et al that genistein obviously decreased SRC phosphorylation in prostate cancer cells (38). A recent report unveiled that repressing SRC activation attenuated ox-LDL-induced lipid accumulation and foam cell formation in VSMCs (39). Concordantly, Lang et al demonstrated that the downregulation of SRC correlated to the reduced proliferation and migration of hydrogen peroxide-exposed VSMCs (40).…”
Section: Discussionsupporting
confidence: 53%
“…VEGF and its receptor VEGFR played an important role in the development of TNBC, and VEGFR was mainly taken as the target and VEGF121, which had a high affinity with VEGFR, seemed to be an ideal tracer (33). It was reported that down-regulation of TLR5 expression could promote proliferation, invasion, and metastasis of TNBC, and TNBC overexpressed VEGF and VEGFR (34). In this study, we confirmed that the expression of VEGFR in 4T1 cells was increased when the expression of TLR5 was down-regulated, suggesting that the down-regulation of TLR5 had an influence on the increase of angiogenesis.…”
Section: Discussionmentioning
confidence: 99%